Scaling like behaviour of resistivity observed in LaNiO3 thin films grown on SrTiO3 substrate by pulsed laser deposition. (16th November 2015) - Sergeenkov, S; Cichetto, L; Zampieri, M; Longo, E; Araújo-Moreira, F M
Abstract: We discuss the origin of the temperature dependence of resistivity ρ observed in highly oriented LaNiO3 thin films grown on SrTiO3 substrate by a pulsed laser deposition technique. All the experimental data are found to collapse into a single universal curve for the entire temperature interval ( K) with being the onset temperature for triggering a resonant scattering of conduction electrons by spin fluctuations in LaNiO3 /SrTiO3 heterostructure.